Journalism and media studies in Lebanon - Melki, Jad (2009)
This study uses mixed-methods to map out the field of journalism and media studies in Lebanese universities and deploys a Q-technique to capture faculties’ opinions. The Q-analysis of 29 instructors revealed three groups of opinions towards journalism studies: one advocated a professional approach, one preferred a communication arts focus, and one pushed for a theoretical and research-intensive orientation. While the three groups differed on various matters, they all agreed that journalism and media studies in Lebanon urgently needed more qualified faculty, locally oriented research, and relevant academic and technical resources. Student demographic analysis revealed a stable increase in broadcast journalism and public relations (PR) enrolments but a decrease in print journalism; advertising and marketing were the most popular subjects, followed by broadcast journalism and PR; females outnumbered males; and the Lebanese University, the only public university, remained the most prestigious and popular program despite its dire financial situation. The curricula analysis found most programs had either a practical or a liberal-professional orientation, while only one had a liberal emphasis. In addition, most programs required an internship, while only two required a thesis; English and the US academic system dominated; only one program offered online journalism; while none offered media or news literacy.